(untitled) (Research, Society and Development, 2025)
Introduction: Lp(a) is a lipoprotein structurally similar to LDL, primarily composed of ApoB-100 and apolipoprotein(a). It is widely recognized as a risk factor for cardiovascular diseases due to its influence on atherosclerotic, inflammatory, and thrombogenic processes. Objective: The objective of this research is to conduct a literature review on lipoprotein(a), the pathophysiological mechanisms involved in the development of atherosclerotic lesions, its current clinical use, and an overview of therapeutic approaches. Method: A narrative literature review was conducted using the following databases: PubMed, Cochrane, JAMA, and Scielo. The search included the keywords: “Lipoprotein(a),” “Atherosclerosis,” and “Cardiovascular Diseases.” A total of 78 studies published in the last 40 years in English were selected based on their relevance to the topic. Results and Discussion: Lp(a) accumulates in atherosclerotic lesions, binds to the extracellular matrix, and transports oxidized phospholipids, promoting inflammation, endothelial dysfunction, and plaque instability. Additionally, it interferes with fibrinolysis and enhances platelet aggregation, favoring thrombosis. Studies highlight that elevated Lp(a) levels are associated with a higher risk of atherosclerotic disease, establishing it as an independent biomarker for cardiovascular events. Current guidelines recommend measuring Lp(a) at least once in a lifetime. Conclusion: Lipoprotein(a) [Lp(a)] is recognized as an independent biomarker and a significant cardiovascular risk factor, implicated in the pathophysiology of atherosclerosis, thrombogenicity, and vascular inflammation. Targeted therapies have emerged as promising alternatives; however, gaps remain regarding whether the therapeutic reduction of Lp(a) effectively prevents cardiovascular events.